UJI DAYA HAMBAT EKSTRAK ETANOL DAUN KEMBANG SEPATU (Hibiscus rosa-sinensis L) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Kairupan, Christy Priskila (PHARMACON, 2014)
The prevalence of diarhea in Indonesia is considered high and one cause is Escherichia coli. The aim of this research was to determine anti-bacterial inhibition, effective concentration, and the effect of increasing concentration of ethanol extract of Hibiscus rosa-sinensis to the growth of E. coli. Extract of H. rosa-sinensis was obtained by masseration using 95% ethanol as solvent. Bacterial growth inhibition employed Kirby-Bauer Method using agar diffusion through wells. Measurement of bacterial inhibition was analysed using one way anova and continued with Least Significantly Difference. Anova showed inhibition by 5%, 10%, 20%, 40%, 80% of extracts. Effective concentrations occured on 20% and 40%. The increasing of extract concentration showed correlation with the increasing of inhibition zone diameters. Â Key words : Hibiscus rosa-sinensis leaf, ethanol extract, inhibition, E. coli